Perwujudan Maqashid syariah Dalam Ekonomi Islam, Lembaga Keuangan Syariah, dan Undang-Undang Nomor 21 Tahun 2008 Tentang Perbankan Syariah - Anisa, Fitri; Hasanudin , Muhammad; Hakim , Atang Abd (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2024)
Maqashid syariah refers to the goals or purposes underlying Islamic laws, and in an economic context, this concept helps determine economic principles and practices that are in accordance with Islamic teachings. This article outlines the objectives of Maqashid syariah which include the protection of religion, life, intellect, lineage and property. This article also discusses various sharia economic instruments used in mudarabah, musharakah and takaful practices. Apart from that, this article aims to determine the important role of sharia financial institutions in achieving the goals of Maqashid syariah in an economic context. The methodology in this article uses library research or literature study with data sources coming from books, journals and research reports that discuss the realization of maqashid sharia in Islamic economics. The results of this article show that the realization of maqashid sharia in Islamic economics can be seen from the implementation of contracts in sharia financial institutions whose operations are based on Islamic values which aim to achieve shared mashlahah which is also supported by the enactment of law number 21 of 2008 concerning sharia banking. which contains maqashid sharia values. The embodiment of hifdz al-maal (protecting assets) is found in mudharabah and musyarakah contracts and the embodiment of hifdz al-khams (protecting the soul) is found in takaful or sharia insurance.